2017
DOI: 10.1007/s10811-017-1112-8
|View full text |Cite
|
Sign up to set email alerts
|

Minimising losses to predation during microalgae cultivation

Abstract: We explore approaches to minimise impacts of zooplanktonic pests upon commercial microalgal crops using system dynamics models to describe algal growth controlled by light and nutrient availability and zooplankton growth controlled by crop abundance and nutritional quality. Losses of microalgal crops are minimised when their growth is fastest and, in contrast, also when growing slowly under conditions of nutrient exhaustion. In many culture systems, however, dwindling light availability due to self-shading in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 59 publications
0
12
0
1
Order By: Relevance
“…It may lead to virus reduction in wastewater or could help protect the viruses from various inactivation processes, thereby further contributing to the waterborne transmission of the pathogenic viral particles [ 128 ]. Further, microalgae also serve as the base of aquatic food webs and fed upon by various predators like zooplanktons and protozoa; particularly the rotifers, copepods, and ciliates [ 129 ]. The predation of microalgae may aid in the removal of viruses which are trapped onto the microalgal EPS or adhered by the electrostatic interactions.…”
Section: Microalgae-based Approaches; An Underexplored Biological Trementioning
confidence: 99%
“…It may lead to virus reduction in wastewater or could help protect the viruses from various inactivation processes, thereby further contributing to the waterborne transmission of the pathogenic viral particles [ 128 ]. Further, microalgae also serve as the base of aquatic food webs and fed upon by various predators like zooplanktons and protozoa; particularly the rotifers, copepods, and ciliates [ 129 ]. The predation of microalgae may aid in the removal of viruses which are trapped onto the microalgal EPS or adhered by the electrostatic interactions.…”
Section: Microalgae-based Approaches; An Underexplored Biological Trementioning
confidence: 99%
“…Slowest zooplankton growth was observed under high light/P ratio [117]. Flynn et al (2017) also reported through predictive modeling that low level of P stress can be strategically applied to create suboptimal conditions to zooplankton growth without causing detrimental conditions for algal growth [118]. Another potential strategy to control certain type of predators is use of high level of CO 2 in the culture medium.…”
Section: Pond Crashes and Mitigationmentioning
confidence: 99%
“…Also, changes in food quality resulting from alterations in the quantity or ratio of nutrients in the culture medium may influence rotifer population dynamics [12]. For instance, Flynn et al [69] modeled the influence of varying microalgal C/N/P ratios on the invasion success of predators and the resulting predator-prey dynamics in intensive microalgae production cultures [69]. Cultures with microalgae having low N/C and/or P/C ratios reduced predator growth and experienced less biomass losses.…”
Section: Modeling Of Impact Of Rotifer Contamination On Microalgae Production In Three Types Of Cultivation Systemsmentioning
confidence: 99%